2010
DOI: 10.1148/radiol.2541090675
|View full text |Cite
|
Sign up to set email alerts
|

Primary Breast Carcinoma: Association of Mammographic Calcifications with Osteopontin Expression

Abstract: OPN could play a role in the formation of calcifications that often are associated with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Howland and coworkers reported that HER2 positivity is recognized to be associated with a higher incidence of LN metastases [23]. Several factors, including a higher ER-positivity rate, the prevalence of c-myc expression [24], as well as the elevated expression of osteopontin [25] and the ryanodine receptor 3 gene [26], were believed to contribute to the microcalcifications. Several factors, including HER2 positivity [23], the number of a CK19 mRNA copies [27], an elevated expression of osteopontin [25], T size and LVI [27], tumor grade [28], and clinical stage [28] were believed to contribute to lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howland and coworkers reported that HER2 positivity is recognized to be associated with a higher incidence of LN metastases [23]. Several factors, including a higher ER-positivity rate, the prevalence of c-myc expression [24], as well as the elevated expression of osteopontin [25] and the ryanodine receptor 3 gene [26], were believed to contribute to the microcalcifications. Several factors, including HER2 positivity [23], the number of a CK19 mRNA copies [27], an elevated expression of osteopontin [25], T size and LVI [27], tumor grade [28], and clinical stage [28] were believed to contribute to lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…HER2-positive status (IHC 3+ or Fish+ and IHC 0/1+ or Fish-) was defined by the 2013 American Society of Clinical Oncology/College of American Pathology guidelines in our study [25, 35]. …”
Section: Methodsmentioning
confidence: 99%
“…High levels of OPN have been detected in calcifications of both benign and malignant breast tissues [82]. Calcifications are more frequent in tumours overexpressing OPN than in OPN – tumours [83]. Although the significance of the presence of OPN in these calcifications is uncertain, in terms of whether OPN promotes or inhibits their formation, it may mean that some OPN‐expressing tumours are more readily detectable at early stages on the basis of associated abnormal or irregular mammographic calcifications.…”
Section: Effect Of Opn On the Tumour Microenvironmentmentioning
confidence: 99%
“…In addition, the detection and characterization of calcifications are important in preoperative evaluations of lesion extent and surveillance after treatment in breast cancer patients 3 , 4 . There are well-established diagnostic criteria based on morphology and distribution of the calcifications at radiologic examination 5 , 6 . Evidence suggests that calcifications affect the prognosis of breast cancer, such that breast cancers with calcifications are predicted to be more aggressive and have worse prognosis than those without calcifications 7 13 .…”
Section: Introductionmentioning
confidence: 99%